The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3109/14767058.2012.697944
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-pH monitoring and conventional pH monitoring are complementary methods to detect association between gastroesophageal reflux and apnea-related symptoms in preterm infants and neonates

Abstract: Addition of MII-pH monitoring to conventional pH monitoring improves the diagnostic yield of symptom association analysis in preterm infants and neonates with apnea-related symptoms. Conventional pH monitoring is still important in the era of impedance measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…Previous results have shown that acid refluxes are present in infants, even in newborns, and suggest they are responsible for pathological consequences, including laryngitis (Cresi et al, 2013;Jadcherla et al, 2011;López-Alonso et al, 2006;Shin et al, 2012;Vermeylen et al, 2005). However, our results may not apply to reflux laryngitis secondary to weakly acid reflux, which are especially prominent in newborns.…”
Section: Reflux Laryngitis Modelcontrasting
confidence: 51%
“…Previous results have shown that acid refluxes are present in infants, even in newborns, and suggest they are responsible for pathological consequences, including laryngitis (Cresi et al, 2013;Jadcherla et al, 2011;López-Alonso et al, 2006;Shin et al, 2012;Vermeylen et al, 2005). However, our results may not apply to reflux laryngitis secondary to weakly acid reflux, which are especially prominent in newborns.…”
Section: Reflux Laryngitis Modelcontrasting
confidence: 51%
“…pH-only events may depend on immature peristalsis of the esophagus, lower LES tone, and delayed gastric empting (thus, explaining their increased frequency among preterm infants compared with older children and adults) or to other factors such as reflux esophagitis, insignificant bolus size, or slow pH drift. 22,29 We speculate that: (1) infants with BPD might have impaired esophageal motility, decreased basal LES tone, and increased LES relaxations, as pointed out by others 5 ; and (2) patients with BPD could be more sensitive than infants without BPD to the autonomic nervous system responses triggered by pH-only events that result in clinical symptoms. The latter point could be explained by the hypothesis that the esophageal afferent neural pathways might be more reactive to decreases in pH among patients with BPD because of their increased inflammatory state.…”
Section: Discussionmentioning
confidence: 90%
“…Proper location of the probe was identified as 2-3 cm above the left diaphragm. [20][21][22] The pH-MII probe was securely taped and connected to the Ohmega system; constant observation and review of the position at the end of the study were assured. pH-MII data were evaluated using manufacturer's software, and each tracing was manually reviewed and validated by the same operator (S.N.…”
Section: Ph-mii Methodsmentioning
confidence: 99%
“…The proportion of nonacid reflux episodes relative to the total number varies from 45% to 90% in infants and children [7,13,14,15,16]. Nonacid reflux is especially prevalent in infants because of pH buffering associated with frequent milk intake.…”
Section: Significance Of Nonacid Refluxmentioning
confidence: 99%
“…It was developed to evaluate the movement of fluid, solid, and air in the esophagus regardless of its pH [5]. Combined multichannel intraluminal impedance-pH (MII-pH) monitoring has been used for the detection of reflux in children since 2002 [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%